Iconic Turn in Deontic Wor(l)ds. From Visual Rules to Optical Dispositives - Siniscalchi, Guglielmo (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
These pages are a brief contribution dedicated to the exploration of the relevance of images for legal discourse. Considering the specific field of road traffic regulation, the paper shows, starting from Michel Foucault’s seminal research on the concept of “dispositive”, how the use of images produced by visual devices such as surveillance cameras or satellite navigators has gradually integrated legislation mainly composed of “graphic rules” (road signs). A passage destined to create a new order of an extra-legal nature that profoundly affects the construction of new forms of subjectivity. Keywords: Dispositive; Foucault; Visual rules; Agamben; Traffic signs Index: 1. Was ist ein normatives Bild? – 2. What is a (optical) dispositive? – 3. Omnes et singulatim: The power of the gaze – References